(untitled) (Journal of Informatics Education and Research, 2026)
In the competitive, digitally-driven marketplace, the retail industry is transforming as in-store technologies (e.g., self-checkout, augmented reality, AI) are increasingly used to enhance the customer experience. This study analyzes the influence of such technology on customer satisfaction and retention. Using primary data collected via a questionnaire from 400 respondents in Coimbatore, the research employs simple percentage analysis, ANOVA, ranking analysis, and factor analysis. Key findings indicate that a significant majority of shoppers are aware of and prefer stores with in-store technology. The most used technology is self-checkout kiosks, but many respondents reported facing challenges. While technology has a moderate to high impact on loyalty for many, a majority of consumers are neutral about revisiting a store based solely on the technology offered. The study suggests that technology must be integrated with overall service quality to drive consistent referrals and long-term customer retention.